Nutritional Composition, In Vitro Antioxidant Activity and Phenolic Profile of Shortcrust Cookies Supplemented by Edible Flowers - Šťastná, Kristýna; Sumczynski, Daniela; Yalcin, Erkan (Foods (Basel, Switzerland), 2021)
In this study, the changes in nutritional composition, phenolic compounds and antioxidant activity in free and bound fractions of shortcrust cookies were investigated. By incorporating ingredients such as kamut, matcha tea, dried mango and jasmine flowers, the contents of crude and neutral-detergent fibre reached up to 2.0% and 5.0%, respectively. Similar increments were observed in phenolic compound contents and 2,2-diphenyl-1-picrylhydrazyl scavenging activity values. Concerning cookies supplemented with matcha tea, the total phenolic compound content raised from 1.0 to 4.8 mg gallic acid equivalent/g and the antioxidant activity value increased from 0.5 to 5.7 mg trolox equivalent/g on a dry weight basis. For determining the antioxidant activity values in water-soluble and insoluble phenolic fractions of the cookies, a photochemiluminiscence assay was separately applied, and they were found up to 0.8 mg ascorbic acid equivalent/g and 3.2 mg trolox equivalent/g, respectively. The main phenolic compounds in all supplemented cookies were neochlorogenic, gallic and vanillic acids.
Keywords: biscuit; phenolic acid; flower; flavonoid; free phenolic; photochemiluminiscence assay; antioxidant capacity; bound phenolic